Порівняльний аналіз результатів апроксимації спіралеподібних ДПК у полярній системі координат спіралями різної форми - Щербина, Віктор Михайлович; Щербина, Виктор Михайлович; Shcherbyna, Viktor; Мацулевич, Олександр Євгенович; Мацулевич, Александр Евгеньевич; Matsulevych, Oleksandr (My University, 2019)
UK: Розв’язання задач апроксимації спіралеподібних та замкнених дискретно представлених кривих (ДПК) напряму пов’язане із застосуванням декартової системи координат для знаходження оптимального рішення за визначеним критерієм, який задовольняє вимогам завдвння. Застосування декартової системи координат для вирішення поставлених задач призводить до отримання результатів з похибкою, оскільки присутня неоднозначність визначення спіралеподібної ДПК. Використання полярної системи координат при розв’язанні задач апроксимації спіралеподібних та замкнених ДПК дозволяє уникнути неоднозначності стосовно вісі Оу та значно спростити математичний апарат для моделювання пропонованих кривих. В роботі розглядається можливість апроксимації спіралеподібних дискретно представлених кривих (ДПК) в полярній системі координат за критерієм найменших граничних відхилень (НГВ) спіралями різної форми. RU: Решение задач аппроксимации спиралевидных и замкнутых дискретно представленных кривых (ДПК) напрямую связано с применением декартовой системы координат для нахождения оптимального решения по определенному критерию, который удовлетворяет требованиям задания. Применение декартовой системы координат для решения поставленных задач приводит к получению результатов с погрешностью, поскольку присутствует неоднозначность определения спиралевидной ДПК. Использование полярной системы координат при решении задач аппроксимации спиралевидных и замкнутых ДПК позволяет избежать неоднозначности относительно оси Оу и значительно упростить математический аппарат для моделирования предлагаемых кривых. В работе рассматривается возможность аппроксимации спиралевидных дискретно представленных кривых (ДПК) в полярной системе координат по критерию наименьших предельных отклонений (НПО) спиралями разной формы. EN: Mathematical processing of discretely submitted graphic information is connected to the decision of tasks of approximation of dot lines in polar system of coordinates by criterion which is not differentiated. The task is complicated that curve (DSC) which represents itself as an illustration of the process proceeding, as a rule, oscillation is discretely submitted, and on the conditions, the describing phenomenon or process, oscillation should not be. The decision of tasks of approximation of helicoid and closed discretely submitted curves (DSC) directly is connected to application of the cartesian system of coordinates for a presence of the optimum decision by the certain criterion which meets the requirements of the decision of a task. Modelling ambiguous, in relation to an abscissa axis, the helicoid or closed discretely submitted curves in the cartesian system of coordinates is connected to increase in number of parameters, causes complications of the computing device and to decrease in accuracy of designing. Use of polar system of coordinates at the decision of tasks of approximation helicoid and closed DSC allows to avoid ambiguity concerning an abscissa axis and considerably to simplify the mathematical device for modelling suggested curves. Existing, perspective, ways and additional opportunities of discrete modelling which take into account internal geometry DSC disregard a question of correction oscillation parts DSC. In work the opportunity of approximation of helicoid discretely submitted curves (DSC) in polar system of coordinates by criterion of the least maximum deviations (LMD) is examined by spirals of the different form and the comparative analysis of results modeling is carried out. In work the opportunity of approximation of helicoid discretely submitted curves (DSC) in polar system of coordinates by criterion of the least maximum deviations (MDC) is examined by spirals of the various form and the comparative analysis of results of modelling is carried spent.
Сравнительный анализ результатов аппроксимации ДПК в полярной системе координат спиралями различной формы
The comparative analysis of results of APPROXIMATION DCS in polar system of coordinates spirals of the various form
Keywords: апроксимація; спіралеподібна дискретно представлена крива (ДПК); простір параметрів; найменші граничні відхилення (НГВ); аппроксимация; спиралевидная дискретно представленная кривая; пространство параметров; наименьшие предельные отклонения; approximation; discretely submitted curve (DCC); space of parameters; the least maximum deviations (LMD)